Experience of tinnitus in adults who have severe-to-profound hearing loss - Alzahrani, Lama (2022)
Funding Information: LA is funded by King Abdul-Aziz University Hospital (KAU), Jeddah, Kingdom of Saudi Arabia. DH and MS are funded through the National Institute for Health and Care Research (NIHR) Biomedical Research Centre programme. The views expressed are those of the authors and not necessarily those of the NIHR, the NHS, the Department of Health, and Social Care. CC is funded by UNICAMP University of Campinas, Brazil, HH is funded by ENT Department, Hospital Cuf Tejo—Nova Medical School, Lisbon, Portugal and finally RD is funded by Sir Peter Mansfield Imaging Centre, School of Physics and Astronomy, University of Nottingham, United Kingdom. The funders had no role in preparation of the manuscript. Publisher Copyright: Copyright © 2022 Alzahrani, Sereda, Chamouton, Haider, Dewey and Hoare.